From triumphalism to maturity : a new exposition to 2 Corinthians 10-13 - Carson, Don A. (Carlisle, UK Paternoster, 1984)
Includes bibliographical references.
Keywords: Bible. N.T. Corinthians, 2nd, X-XIII -- commentaries